Mechanism of Nucleic Acid Sensing in Retinal Pigment Epithelium (RPE): RIG-I Mediates Type I Interferon Response in Human RPE - Joshua Schustak; Michael Twarog; Xiaoqiu Wu; Henry Y. Wu; Qian Huang; Yi Bao (Journal of Immunology Research)
Age-related macular degeneration (AMD), a degenerative disease of the outer retina, is the leading cause of blindness among the elderly. A hallmark of geographic atrophy (GA), an advanced type of nonneovascular AMD (dry AMD), is photoreceptor and retinal pigment epithelium (RPE) cell death. Currently, there are no FDA-approved therapies for GA due to a lack of understanding of the disease-causing mechanisms. Increasing evidence suggests that chronic inflammation plays a predominant role in the pathogenesis of dry AMD. Dead or stressed cells release danger signals and inflammatory factors, which causes further damage to neighboring cells. It has been reported that type I interferon (IFN) response is activated in RPE cells in patients with AMD. However, how RPE cells sense stress to initiate IFN response and cause further damage to the retina are still unknown. Although it has been reported that RPE can respond to extracellularly added dsRNA, it is unknown whether and how RPE detects and senses internally generated or internalized nucleic acids. Here, we elucidated the molecular mechanism by which RPE cells sense intracellular nucleic acids. Our data demonstrate that RPE cells can respond to intracellular RNA and induce type I IFN responses via the RIG-I (DExD/H-box helicase 58, DDX58) RNA helicase. In contrast, we showed that RPE cells were unable to directly sense and respond to DNA through the cGAS-STING pathway. We demonstrated that this was due to the absence of the cyclic GMP-AMP synthase (cGAS) DNA sensor in these cells. The activation of IFN response via RIG-I induced expression of cell death effectors and caused barrier function loss in RPE cells. These data suggested that RPE-intrinsic pathways of nucleic acid sensing are biased toward RNA sensing.